Telemedicine applied to the follow up of patients with End Stage Renal Failure - Pierre SIMON (RDPLF, 2018)
Abstract In the 21st century, renal failure is a chronic disease that affects several millions people in France and around 600 millions worldwide. Its prevalence in the general population increases with the lengthening of the life expectancy that characterizes the developed countries and which begins to appear in the developing countries. Chronic hemodialysis is a treatment that saved many children and young adults in the 20th century whose kidneys were destroyed by several infectious and toxic agents and by untreated malignant hypertension. These causes have been controlled by hygiene measures, anti-infective agents or protective pharmacological agents of the cardiovascular system. Today the causes of end stage renal failure are dominated by degenerative diseases due to aging, such as diabetes and chronic vascular disease. The prevention of the worsening of chronic renal failure is now possible due to better control of high blood pressure and diabetes which are the two main causes of kidney destruction. Hemodialysis treatment cannot always be relayed by renal transplantation. Many patients remain on chronic hemodialysis until they die. It is important to adapt the conditions of treatment to the social life of patients affected by this chronic disease so that these are the best possible. This is the goal of telemedicine that allows to remotely monitor the main clinical and biological factors associated with the worsening of the disease. Teledialysis (hemodialysis and peritoneal dialysis) allows to perform dialysis sessions at home or at the nearest in home substitutes (nursing home) or in satellite units of hemodialysis. Similarly, when the patient is transplanted, it makes possible to either lighten or intensify the surveillance according to the risk or not of graft rejection through home teleconsultation. The tools of the digital era such as telemedicine, health connected with connected objects and mobile apps for medical purposes, the performance of which is increasing with the algorithms of artificial intelligence (machine learning, deep learning), can improve the relationship between the patient and his doctor. An ethical reflection must be associated with all these innovations. New exercise of the medicine will be greatly enriched due to medical time more devoted to the relationship with the patient. The new care organizations made possible by digital technologies must be taught to the new generations of nephrologists.